2019
DOI: 10.21037/hbsn.2018.12.06
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of ovarian cancer liver metastasis

Abstract: In addition to hepatocellular carcinoma, metastatic liver cancer (MLC) is another focus of hepatic surgeon. Good outcome of patients with liver metastasis (LM) from colorectal cancer or neuroendocrine tumor have been achieved. Ovarian cancer liver metastasis (OCLM) has its unique oncological characteristics and a variety of metastasis patterns, which brings a challenge to hepatic surgeon. Hepatic surgeons hold different views and techniques from gynecologists, which makes differences in the evaluation and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…A study of analyzing the safety of laparoscopic secondary cytoreductive surgery in 58 patients with platinum-sensitive recurrent ovarian cancer showed that the median PFS was 28.0 months and the 2 year OS was 90.7% (26). Wang et al found that the OS of ovarian cancer patients with liver metastases who received R0 liver resection and cytoreductive surgery were 50.1 months, however, the OS of patients who received R0 cytoreductive surgery and non-R0 liver resection was 20.0 months (27). Some selected patients with cytoreductive surgery and liver resection had better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A study of analyzing the safety of laparoscopic secondary cytoreductive surgery in 58 patients with platinum-sensitive recurrent ovarian cancer showed that the median PFS was 28.0 months and the 2 year OS was 90.7% (26). Wang et al found that the OS of ovarian cancer patients with liver metastases who received R0 liver resection and cytoreductive surgery were 50.1 months, however, the OS of patients who received R0 cytoreductive surgery and non-R0 liver resection was 20.0 months (27). Some selected patients with cytoreductive surgery and liver resection had better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic surgeons are responsible for assisting gynecologists in improving the prognosis of patients. Wang et al reported that the OS time of patients with OCLM who received R0 laparoscopic liver resection (LR) was 50.1 months, which was significantly higher than that of patients who received non-R0 LR (20.0 months) when the primary OC received cytoreductive surgery (CRS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dissemination (PD), as the most common pattern, usually leads to tumor implantation in the liver capsule, hepatorenal recess and hepatic diaphragm (right diaphragms to hepatic capsule), which might be caused by the continuous clockwise movement of OC cancer cells with intestinal peristalsis and ascites. 15,16 The incidence of PD is 40-90% and does not invade liver parenchyma, indicating OC stage III. 4,16 The incidence of diaphragmatic metastasis in advanced or recurrent OC is also very high, about 20-40%, even as high as 91%.…”
Section: Pattern and Clinical Featuresmentioning
confidence: 99%